Katılımcı liderlik, Duygusal Bağlılık ve İş Tatmini İlişkisi: Örgütsel Güvenin Aracılık Rolü(The Relationship Between Participative Leadership, Affective Commitment and Job Satisfaction: The Mediating Role of Organizational Trust) - Sökmen, Alev; Yazıcıoğlu, İrfan; Kenek, Gökhan (Journal of Business Research - Turk, 2021)
Purpose – In this study, the effects of participative leadership on affective commitment and job satisfaction are examined; It was aimed to determine the mediating role of organizational trust between participative leadership and emotional commitment, and participative leadership and job satisfaction. Design/methodology/approach – Relational scanning model was used in this research. The data were obtained by using a questionnaire method with 304 food and beverage employees from accommodation businesses operating in Antalya province and selected by simple random sampling method. SPSS 26 was used for descriptive statistics, reliability tests, correlation analysis, simple linear and multiple linear regression analysis. Findings – According to the results of the analysis, it is seen that organizational trust and participative leadership have a significant effect on affective commitment and job satisfaction. It has been determined that participative leadership also has a significant effect on organizational trust. In addition, it has been observed that organizational trust has a partial mediating role between participative leadership and affective commitment, and a full mediating role between participative leadership and job satisfaction. Discussion –These results show that food and beverage employees working in accommodation businesses are sensitive to participative leadership practices. It can be stated that the participative leadership approach enables the employee to have trust in the organization, to develop an affective belonging/commitment to his organization, which he/she thinks has an impact on the decisions made, and to be satisfied from job. In this context, it is thought that the implementation of managerial methods that increase the participation of employees in decisions will have positive outcomes in both individual and organizational terms.
Keywords: 8. Economic growth; 16. Peace & justice